Analisis Kontribusi Pendapatan Sektor Pariwisata terhadap Pendapatan Asli Daerah Kabupaten Gianyar - Mardiana, Gusti Ayu Herlin (E-Jurnal Akuntansi, 2021)
This study analyzes three variables, namely Gianyar Regency PAD, PHR and retribution for recreation and sports. The analytical tool used in this study is contribution analysis, linear regression. This study uses secondary data, so that the data collection method used is the method of non-participant observation. Based on the results of the analysis, it is known that the contribution of tourism sector revenues from PHR and retribution for recreation and sports reached an average of 44.71 percent during 2002-2017. The results of this study can be a reference for the Gianyar Regency Government that revenue from the tourism sector has a large contribution to the Gianyar Regency PAD, so the Gianyar Regency Government is increasingly motivated to continue to improve facilities and infrastructure in the tourism sector that can support increased income from the tourism sector. Keywords: Hotel And Restaurant Tax; Retribution For Recreation And Sports; Local Revenue.